Nurses’ Perceptions of Patient Safety Culture at King Khaled University Hospital, Saudi Arabia - Al-Amri, Mohammed; ALMendeil, Mazin (The Arab Journal of Administration, 2020)
The aim of this study is to assess the perception of nurses towards patient safety culture at King Khalid University Hospital (KKUH) in Saudi Arabia. To achieve this aim, the study utilized a questionnaire developed by the Hospital Survey On Patient Safety Culture (HSOPSC) (2008) and includes (34) items that measures patient safety culture on the patient safety culture dimensions. This questionnaire has been distributed to a sample consists of (250) nurses. A total of (199) complete questionnaires has been received back at a response rate of (80%). After analyzing data and testing questions, the study revealed: (1) the dimension of highest positively is teamwork within units (2) the dimension of lowest positively is hospital hands-off and transitions (3) the study revealed that there are statistically significant differences in the response of the respondents on the differences between the nurses perception of patient safety culture due to some personal characteristics (age, educational qualification, and years of experience) and (4) the study found that (64%) of the study sample indicated the absence of any reports on medical errors. Based on these results, certain recommendations were suggested.